Is there a secular trend regarding puberty in children with down syndrome? - Erdoğan, Furkan; Güven, Ayla (Frontiers in Endocrinology, 2022)
Introduction: There are very few studies on the age of onset and end of puberty in children with Down syndrome. Information on the course of puberty in children with Down syndrome compared to their healthy peers is limited. In addition, there is limited information on the effects of factors such as obesity and hypothyroidism that affect the puberty process in children with Down syndrome. Our aim in our study is to determine whether the pubertal development of children with Down syndrome (DS) differs from their healthy peers and from previous studies conducted with DS children. Methods: The medical records of DS children were examining retrospectively. The anthropometric measurements and the age of onset of pubertal stages, and menarche were recorded. Results: Of the 140 Down syndrome patients followed in our clinic, 51 of whom had started puberty constituted the study group. The mean age of onset of puberty was 10.3 ± 1.0 years in our group (10.0±0.8 years for girls, 10.6±1.2 years for boys, respectively). 46% of pubertal girls with DS were obese. The age of menarche in girls with DS was 11.8 ± 0.7 years. The menarche age of girls with DS was significant difference than healthy girls. In the DS boys, only the Tanner V stage ages were different from the healthy children. True- precocious-puberty was detected in three children. Conclusion: Although breast development begins later in females with DS than their healthy peers; menarche is detected earlier than their peers and tendency towards obesity as in the whole population. While the age of pubertal onset was similar to healthy children in male patients, our findings suggest that their puberty duration is longer. We also emphasize that studies with larger numbers of patients are needed to better understand the puberty process in children with DS.